2023
DOI: 10.3390/plants12132419
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus cabrialesii: Five Years of Research on a Novel Species of Biological Control and Plant Growth-Promoting Bacteria

Karem Ma. Figueroa-Brambila,
Alina Escalante-Beltrán,
Amelia Cristina Montoya-Martínez
et al.

Abstract: Bacillus cabrialesii is a novel bacterial species isolated from wheat (Triticum turgidum L. subsp. durum) plants in the Yaqui Valley, Mexico, by our research team. Over years of research studying this strain at the cutting-edge level, it has shown different mechanisms of action. B. cabrialesii is strongly reported as a plant-growth-promoting bacterium and a biological control agent on wheat crops. Knowing this, B. cabrialesii has been brought from lab to field as part of a bacterial consortium, not to mention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The planting properties of PPC can be improved by other means [20]. Bacillus is a kind of bacteria that can produce spores.…”
Section: Introductionmentioning
confidence: 99%
“…The planting properties of PPC can be improved by other means [20]. Bacillus is a kind of bacteria that can produce spores.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the DT wheat variety is more resistant to drought than DS variety: drought decreased the length of seedlings, biomass, and leaf Chl content of DT variety significantly less than DS variety (Table 1). The ability of PGPB to mitigate drought-caused damages in various plants, including wheat, are well documented [21,23,28,29,[63][64][65]. However, the knowledge about the responses of drought-tolerant and susceptible wheat genotypes upon endophytic PGPB treatment is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…After testing the biocontrol of several Bacillus strains against F. languescens CE2, B. cabrialesii subsp. tritici TSO2 T was selected as BCA for additional in vitro assays, due to its previously reported potential as a biocontrol bacterium and its swarming motility [24,28,30]. Thus, the radial growth of the fungal colonies was recorded every 24 h for ten days (Figure 6).…”
Section: Biocontrol Assay By Confrontation In Vitromentioning
confidence: 99%
“…As an example of disease management, B. thuringiensis is a soil bacterium that produces spores, which contain crystals that possess strong and targeted insect-killing capabilities [23]. Likewise, strains of B. cabrialesii, a bacterial species recently discovered which is widely reported as a BCA and plant growth promoter [24]. In this sense, the genus Bacillus inhibits the proliferation of phytopathogens through the synthesis of growth-suppression molecules, such as cell wall-destructive enzymes, antibiotics, lipopeptide biosurfactants, or by triggering defense signals in plants [25][26][27].…”
Section: Introductionmentioning
confidence: 99%